Stylistics of the literary word: the results of scientific analyses and new research findings (Eurasian Journal of Philology Science and Education, 2024)
The study and systematization of the history of science lay the foundation for generating new ideas. Knowledge of the scientific past opens pathways to understanding the present, allowing for further differentiation and in-depth analysis of the challenges in the field. In Kazakh linguistics, the stylistics of literary language has primarily been examined in relation to the development of the Kazakh literary language, the differentiation of functional styles, the role of expressive means in prose, and the distinctive language and style of individual writers.The article systematizes the main conclusions in the study of the language and style of the prose genre in World linguistics, Turkology and Kazakh linguistics. The relevance and importance of studying the objects and methods of artistic word Stylistics in combination with aspects of anthropospecific linguistics, linguocretism of the writer, communicative stylistics and word culture are substantiated.The main idea and purpose of the study is, firstly, to systematize in the form of a review the main conclusions about the problems of general Stylistics, including artistic word Stylistics. Artistic Stylistics in the Kazakh language was considered in the aspects of the characteristics of the development of the Kazakh literary language, the differentiation of functional styles, the function of means of expression in the prose genre, the language and style of individual writers.At the present stage, the problems of the culture of the word are deepened, while it is important to determine the communicative quality of the word, the communicative target, along with the correct, appropriate use of the word. Analysis, interpretation, evaluation of Kazakh art using the methods of these branches of science makes a theoretical and practical contribution to the development of general Stylistics, including Kazakh linguostilistics.Key words: literary word, linguistic stylistics, fiction, word usage, analysis, interpretation, evaluation.